Tumores testiculares na infância - Teixeira,Roni Leonardo (2009)
Testicular and paratesticular prepuberal tumors are rare. They represent around 1% of the total of tumors of infancy. They subdivide in 2 groups: germ cells tumors and non germ cells tumors, being able to occur in all the ages, and about 75% are malignant, and about 19% of these they present metastasis. The tumors of germ cells tumors represent 60 75% of the tumors testiculars in infancy, having as main example the yolk sac tumor (65% of the neoplasms), followed for teratomas (14%); although some works to exist where teratoma, if presents as most common .The non germ cells tumors include the Leydig cell tumor and Sertoli cell tumor. The Leydig cell tumor, are most frequent between the non germ cells tumors testicular. This review article on epidemiology, diagnosis and treatment of to testicular and to paratesticular tumors in child.